2014
DOI: 10.1142/s0217751x14500948
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field effects on p-wave phase transition in Gauss–Bonnet gravity

Abstract: In the probe limit, we study the holographic p-wave phase transition in the Gauss-Bonnet gravity via numerical and analytical methods. Concretely, we study the influences of the external magnetic field on the Maxwell complex vector model in the five-dimensional Gauss-Bonnet-AdS black hole and soliton backgrounds, respectively. For the two backgrounds, the results show that the magnetic field enhances the superconductor phase transition in the case of the lowest Landau level, while the increasing Gauss-Bonnet p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Interestingly, the results showed that due to the nonminimal coupling between the vector field and the Maxwell field, the increasing magnetic field can induce superconductor phase transition even without charge density, which is similar to the QCD vacuum instability triggered by the strong magnetic field to develop the ρ-meson condensate [15]. Moreover, the investigation about the response of the external magnetic field on the p-wave phase transition also showed that the SU(2) YM model is a special case of the MCV model in five-dimensional (5D) soliton and 4D Lifshitz black holes [16][17][18]. Furthermore, considering the backreaction, the MCV model exhibits the rich phase structures, especially "retrograde condensation" [19][20][21].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Interestingly, the results showed that due to the nonminimal coupling between the vector field and the Maxwell field, the increasing magnetic field can induce superconductor phase transition even without charge density, which is similar to the QCD vacuum instability triggered by the strong magnetic field to develop the ρ-meson condensate [15]. Moreover, the investigation about the response of the external magnetic field on the p-wave phase transition also showed that the SU(2) YM model is a special case of the MCV model in five-dimensional (5D) soliton and 4D Lifshitz black holes [16][17][18]. Furthermore, considering the backreaction, the MCV model exhibits the rich phase structures, especially "retrograde condensation" [19][20][21].…”
Section: Introductionmentioning
confidence: 84%
“…[2,3,10,14,17,18], in the absence of the spatial component of the gauge field A y (r), i.e., the superconductor model, the system always suffers the second-order phase transition in the probe limit. However, with the presence of A y (r) in the superfluid model, we find that the phase transition will switch from the second order to the first order in the case of a sufficiently high superfluid velocity.…”
Section: Sy µmentioning
confidence: 99%
See 2 more Smart Citations
“…Other generalized investigations based on this new p-wave model can be found, for example, in Refs. [55][56][57][58][59][60][61]. Considering the increasing interest in study of the holographic p-wave model, we will also extend the study to the holographic pwave superconductor with hyperscaling violation, which has not been constructed as far as we know.…”
Section: Introductionmentioning
confidence: 99%